FLOW ENGINEERING TO REMEDIATE CONTAMINATED WATER QUALITY DUE TO DOMESTIC WASTE DISPOSAL IN BELIK RIVER, YOGYAKARTA - Slamet Suprayogi; Aulia Nur Fitriyani; Venny Vivid Fadhilah (Universitas Negeri Medan, 2022)
The Belik River Basin is located in an urban area and is affected by rapid population growth. Belik River flows from north of the UGM campus (Karangwuni Subvillage in Caturtunggal, Depok, Sleman) to Umbulharjo District then feeds into Gajah wong River before emptying into Opak River. This study sought to examine the effects of flow engineering on the quality of domestic waste-contaminated waters. The flow engineering is in the form of a small weir or pile of stones aiming to elevate the upstream water level and create a free fall or plunge that aerates the overflowing water. The water was sampled from four river segments twice: upstream and downstream of the designed weir. Water sampling from one element to the next factored in water travel time and settlement density in the surroundings with the assumption that these factors would produce different concentrations of domestic waste. The water quality parameters tested were D.O., BOD, COD, phosphate, nitrate, ammonia, and iron. The results showed that the flow engineering improved water quality in the four segments differently, as evident from some of the decreased or increased parameter values after the plunge. These different effects are influenced by the number of sources of domestic waste pollutants and the dominant land use in each segment. Keywords: Belik River, Small Weir, Aeration